The didactic value of linking models: experiences from the LEI model funnel - John F.M. Helming; Martin Banse (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2008)
The complexity of agri-environmental economic issues is such that a model that is fully consistent at all levels of aggregation and all type of questions to be addressed is not available at the Agricultural Economics Research Institute in the Hague LEI. Such a model is probably also not feasible. At LEI this problem is solved by linking models at different scales of analysis: global economic, national economy-wide, regional agricultural, national spatial and farm levels. This linked model system enlarges scope and consistency of the analysis. The goal of the model linking, however, is not a full integration and, ultimately, simultaneous optimization of the models. Therefore, the different models of the LEI model funnel are often rather loosely linked. Hence, it is not surprising that the models sometimes produce different results even for the shared variables. This article describes the difficulties to share and exchange information between different models and identifies possible solutions which aim at a more consistent analysis along the models combined at LEI while maintaining the diversity of modelling approaches.
Keywords: 330; Agrarpolitik; Wirkungsanalyse; Wirtschaftsmodell